Evaluation of fracture resistance and surface characteristics in monolithic zirconia: a comparative analysis of 3D printing and milling techniques - Rogina M. Hassan; Yomna Ibrahim; Rewaa G. AboELHassan; Amir Shoukry Azer (BMC Oral Health)
Abstract Background The primary method for fabrication of zirconia restorations is subtractive manufacturing technology. This process mills restorations from large blocks using various cutting tools resulting in large amounts of waste material. 3D printing has emerged as an alternative tool for additive manufacturing of zirconia with less waste and high efficiency. Methods A total of 24 monolithic zirconia crowns were divided into: Group I (milled zirconia crowns) and Group II (3D printed zirconia crowns) (n = 12). The crowns were then polished and glazed then subjected to 5000 thermocycles. Fracture resistance for the crowns was measured using universal testing machine followed by estimation of Weibull modulus and characteristic strength. Fractographic analysis was done using scanning electron microscope (SEM). 72 discs (10 mm × 2 mm) were fabricated by milling and printing (n = 36) then subjected to 5000 thermocycles. The discs were used for surface roughness assessment both before (n = 12) and after (n = 12) glazing using contact profilometer and unglazed discs (n = 12) were used for microhardness which was measured by Vickers microhardness tester. Comparisons between study groups were performed using independent samples t-test. Two-way ANOVA was performed to assess the association between material (milled or printed) and glazing (glazed or unglazed) with surface roughness. Significance level was set at P-value < 0.05. Results In comparison to 3D printed zirconia, the milled version exhibited comparable fracture resistance, reduced surface roughness, and increased microhardness. While both groups showed comparable fracture resistance with no significant difference (P = 0.26), the milled zirconia demonstrated significantly better surface finish (P < 0.001) and microhardness (P < 0.001). However, glazing lowered the surface roughness significantly for both milled (P < 0.001) and printed (P = 0.001) zirconia, bridging the gap in surface quality between the two fabrication techniques. Conclusions The enhanced fracture resistance and Weibull modulus of 3D printed zirconia indicate increased reliability and consistency in its mechanical properties. However, limitations of its surface properties highlight the need for further optimization before full clinical adoption.